2003
DOI: 10.1023/b:lahu.0000004888.52210.35
|View full text |Cite
|
Sign up to set email alerts
|

Is There Touch in the Game of Twister®? The Effects of Innocuous Touch and Suggestive Questions on Children's Eyewitness Memory.

Abstract: Preschool children (ages 48-70 months, N = 48) experienced 2 to-be-remembered events (i.e., the games Twister ® and Shapes) that included either innocuous bodily touch or no touch. Participants were interviewed 7 days later and asked direct ("Did Amy kiss you?") or suggestive "tag" questions ("Amy kissed you, didn't she?") equated for content. Results indicated that children who were innocuously touched were no more likely to falsely assent to "abuse-related" touch questions (e.g., "Amy touched your bottom, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…In Saywitz and colleagues' (1991) study, the majority of children who experienced a vaginal and anal examination revealed genital contact only when asked directly about it. In Krackow and Lynn's (2003) study, children who were asked suggestive questions made more errors of commission in response to abuse-touch questions than children who were not asked these questions. These findings suggest that children's reports of innocuous touching vary depending on the way in which they are questioned, at least in analogue contexts.…”
Section: Abstract Investigative Interviewing Bodily Contact Touchinmentioning
confidence: 77%
See 1 more Smart Citation
“…In Saywitz and colleagues' (1991) study, the majority of children who experienced a vaginal and anal examination revealed genital contact only when asked directly about it. In Krackow and Lynn's (2003) study, children who were asked suggestive questions made more errors of commission in response to abuse-touch questions than children who were not asked these questions. These findings suggest that children's reports of innocuous touching vary depending on the way in which they are questioned, at least in analogue contexts.…”
Section: Abstract Investigative Interviewing Bodily Contact Touchinmentioning
confidence: 77%
“…For example, Saywitz, Goodman, Nicholas, and Moan (1991) reported that when five-year-old girls did not actually experience genital touch during a medical examination they almost never made an error of commission when questioned verbally. Similarly, Krackow and Lynn (2003) found that preschool-aged children who were innocuously touched were no more likely to falsely assent to "abuse-related" touch questions (e.g., "Amy touched your bottom, didn't she?") than were children who were not touched.…”
Section: Abstract Investigative Interviewing Bodily Contact Touchinmentioning
confidence: 98%
“…"; "There was a mark on the side of the woman's face, wasn't there?)." All questions were presented in a tag format to increase the chances of obtaining suggestibility (Krackow & Lynn, 2003). After completion of the interview, participants were debriefed.…”
Section: Methodsmentioning
confidence: 99%
“…Because adult touches have been the focus of previous work (e.g., Krackow & Lynn, 2003;Tobey & Goodman, 1992) and often are of significance to forensic investigations, we explored whether children's responses to this item would be affected by interviewer manner. Specifically, we predicted that children questioned by the nonsupportive interviewer would be more likely to report this erroneous event than would children questioned by the supportive interviewer.…”
Section: Studymentioning
confidence: 99%
“…Such touches may be more salient to children than is an innocuous touch to feel vibrations on the throat. A study by Krackow and Lynn (2003) showed that 4-to 6-year-olds were more likely to incorrectly acquiesce to questions about innocuous touches taking place during a game of Twister (e.g., ''Did Amy touch your arm?") than to questions concerning abuse touches (e.g., ''Did Amy touch your bottom?").…”
Section: Interviewing Styles and ''Don't Know" Answersmentioning
confidence: 99%